Students Mathematical Literacy Level in Solving PISA-Based Problems Shape and Space Content: Analysis from the perspective of self-concept mathematics - Pertiwi, Kurnia Jati; Setyaningsih, Nining (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2024)
21st-century learning is learning that makes literacy a major component. Mathematical literacy is the ability of individuals to reason mathematically, formulate, implement, and analyze problems to find a solution in a real-world context. This study aims to analyze the mathematical literacy ability of grade IX students in shape and space content in terms of mathematic self-concept. One of the difficult materials in mathematics is shape and space. The difficulties experienced by students have psychological factors that influence one of them is self-concept mathematics. This study used qualitative research methods with stages of giving tests, filling out questionnaires, and structured interviews. This study's subject was a grade IX A MTs PPMI Assalam Sukoharjo student. Data analysis techniques use techniques from Milles and Huberman by reducing data then presenting data and drawing conclusions. The results obtained from this study are that students with high self-concept mathematics can meet the indicators of formulating problems, using concepts, and analyzing mathematical results in real-world contexts. Students who moderate self-concept mathematics are only able to meet the indicators of formulating problems and using concepts. In contrast, students with low self-concept mathematics are only able to meet indicators using - mathematical concepts.